SIFAT FISIS DAN MEKANIS ANYAMAN BAMBAN (Donax canniformis) DENGAN BAHAN STABILISATOR PEG 1000 DAN TANIN KULIT AKASIA - Harsono, Dwi (Kementerian Perindustrian, 2015)
Bamban (Donax canniformis) is one of the biological resources that grow in the swampy areas and has been used by the community as a raw material in the form of woven handicrafts. Bamban bark that used as raw material woven texture is hard and the surface was very slippery so hard to make. This study was conducted to determine the nature of the characteristics of stem Bamban and determine the effectiveness of the stabilizers PEG 1000 and tannin from extract acacia bark in improving the quality of physical and mechanical properties strands of Bamban. Treatments include immersion with PEG 1000 and acacia bark tannins for 2 hours. Results of the study the effectiveness of treatments of soaking the material stabilizers PEG 1000 and tannins from extract acacia bark all of them can improve the physical and mechanical properties of raw material of Bamban woven handicraft and make it easier for artisans in the process of weaving due to the treated material can make more limp strands of Bamban and not to stiff, in addition to making the product brighter and more attractive.Keywords : bamban, physical properties , mechanical Â properties